Expected Influence of Ethics on Product Development Process - Stig Larsson (tripleC: Communication, Capitalism & Critique)
Product development efficiency and effectiveness is depending on a process being well executed. The actions of individuals included in the processes are influenced by the ethical and moral orientations that have been selected by each individual, whether this selection is conscious or not. This paper describes different ethical choices and the expected effects they may have on the development process exemplified by the product integration process for software products. The different frameworks analyzed are utilitarianism, rights ethics, duty ethics, virtue ethics and ethical egoism. The expected effects on the goals for product integration may be debated. This is a result in it self as it triggers discussions about ethical considerations and increase the awareness of the influence of moral decisions. Our conclusion is that the adherence to specific moral frameworks simplifies the alignment of actions to the practices described in product development models and standards and through this supports a more successful execution of product development projects. This conclusion is also confirmed through a comparison between the different directions and several codes of ethics for engineers issued by organizations such as IEEE as these combine features from several of the discussed ethical directions.